Truncation and constitutive activation of the androgen receptor by diverse genomic rearrangements in prostate cancer - Christine Henzler (Nature Portfolio, 2016)
Castration-resistant prostate cancer frequently presents with persistent androgen receptor signalling. Here, the authors find that the androgen receptor is subject to genetic rearrangements, resulting in variants with ligand-independent activity.